2014
DOI: 10.2196/jmir.3439
|View full text |Cite
|
Sign up to set email alerts
|

Massive Open Online Courses on Health and Medicine: Review

Abstract: BackgroundMassive open online courses (MOOCs) have become immensely popular in a short span of time. However, there is very little research exploring MOOCs in the discipline of health and medicine.ObjectiveWe aim to provide a review of MOOCs related to health and medicine offered by various MOOC platforms in 2013, by analyzing and comparing the various offerings, their target audience, typical length of course, and credentials offered. We also discuss opportunities and challenges presented by MOOCs in health a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
189
0
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(211 citation statements)
references
References 7 publications
8
189
0
14
Order By: Relevance
“…Ideally, the topic should be focused on an area that you are deeply passionate about as this enthusiasm will come across in the resources you develop. However, you need to be realistic and carefully take into consideration your intended target audience and the MOOC (Liyanagunawardena & Williams 2014 administrator would be particularly helpful to coordinate the development of the course and ensure self-imposed, and platform provider, deadlines are kept.…”
Section: Tipmentioning
confidence: 99%
“…Ideally, the topic should be focused on an area that you are deeply passionate about as this enthusiasm will come across in the resources you develop. However, you need to be realistic and carefully take into consideration your intended target audience and the MOOC (Liyanagunawardena & Williams 2014 administrator would be particularly helpful to coordinate the development of the course and ensure self-imposed, and platform provider, deadlines are kept.…”
Section: Tipmentioning
confidence: 99%
“…Although MOOCs have been available for almost a decade, and courses continually becoming available on commercial platforms, there remains a paucity of empirical evidence to support their utilisation. Specifically, within medical education, numerous roles for MOOCs have been proposed for both on-and off-campus learning [7,22,24,26,27,29]; however, a clear rationale for their effective deployment is still nascent. This study focused on the use of a clinical anatomy MOOC by healthcare professionals building on previous research that analysed its use by undergraduate medical students [7].…”
Section: Discussionmentioning
confidence: 99%
“…Across undergraduate and postgraduate medical education, MOOCs have an emerging presence with evidence to support their use as part of blended curricula on campus-based medical course [7], suggestions they could be used as part of flipped classroom approaches [22][23][24], although research from other disciplines suggests this needs serious consideration [25]. Additionally, they have been suggested as an alternative platform for interprofessional education (IPE) [26] or as an online approach to continuing professional development (CPD) [6,[27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in 2014, the U.S. Department of Education endorsed four universities to deliver continuing education units for teachers through MOOCs, allowing school districts a convenient and low-cost way to enhance professional development (Duke Online Education Initiatives 2014). Finally, Liyanagaunawardena and Williams (2014) reported that MOOCs are being implemented more frequently in healthcare and medical fields to increase continuing education for healthcare professionals, provide supplemental courses for healthcare students, and increase health literacy and education for professionals, patients, and the general population. For behavior analysis, future MOOCs could provide supplemental training for school and agency personnel and continuing education units for board certified professionals.…”
Section: Implications Of Moocs For Behavior Analysismentioning
confidence: 99%